The evaluation and management of different grasses and legumes as potential cover crops in the vineyards of South Africa - Fourie, J. C. (Stellenbosch : University of Stellenbosch, 2007)
Thesis (PhD(Agric) (Agronomy))--University of Stellenbosch, 2007